Disease‐duration based comparison of subsets of immune cells in SARS CoV‐2 infected patients presenting with mild or severe symptoms identifies prognostic markers for severity. Issue 2 (16th January 2021) - Kulkarni‐Munje, Archana; Palkar, Sonali; Shrivastava, Shubham; Lalwani, Sanjay; Mishra, Akhilesh C.; Arankalle, Vidya A.
Abstract: Introduction: Infection with SARS‐CoV‐2 leads to a spectrum of symptoms. Understanding the basis for severity remains crucial for better management and therapy development. So far, older age, associated‐comorbidities, and IL‐6 have been associated with severity/mortality. Materials and Methodology: As a primary step, we analyzed the frequency and functional profile of innate immune cells (NK cells/dendritic cells/monocytes) and adaptive immunity‐driving lymphocytes (B cells/T cells/follicular T helper cells) by flow cytometry. Sixty cases of SARS CoV‐2 infection (25 severe, 35 mild) and ten healthy subjects without SARS CoV‐2 IgG were included. Disease‐duration based analysis of immune profile was explored for early events differentiating the two disease forms. Neutralizing antibody titers were determined by PRNT. Results and Conclusion: Disease severity was found to be associated with impaired maturation of mDCs and hyperactivation of NK, follicular T helper cells, and CD8 T cells. Lower IL‐21 receptor expression on memory B cells indicated an imbalance in IL‐21/IL‐21 R ratio. Lower BCMA positive plasmablast cells in severe cases did suggest a probable absence of long‐term humoral immunity. Multivariate analysis revealed a progressive association of PD‐1+CD4 T cells with PRNT50 titers. Thus, in addition to identifying probable prognostic markers for severity, our study emphasizes the definite need for in‐depth viral antigen‐specific functional analyses in a larger patient cohort and with multiple sampling. Abstract : Understanding pathogenesis of severity in current SARS‐CoV2 pandemic is of prime importance. Another concern is the recent observations (including ours) of early, higher neutralizing antibody titers in severe disease. India is reporting >80, 000/day for several weeks now. Identification of prognostic markers for severity may help identifying "extra‐care‐needed" patients. As a first step, this flow‐cytometry based study was planned to understand (1) differences in immunologic modulations in patients with mild and severe disease (2) if we can identify early events associated with severity (3) prognostic markers for severity (4) association of functionality of immune cells with higher antibody titers in severe disease.